Educational projects as a teaching methodology for country education school Sol Nascente of Confresa-MT - Noemia de Souza Ventura; Marcelo Franco Leão (Universidade Federal do Norte do Tocantins, 2018)
Developing educational projects in rural schools can be a viable alternative because it provides moments of great learning to the subjects involved. In order to highlight the need to develop teaching methodologies for Rural Education, this study aimed to use educational projects as an alternative to attend to this clientele. The study, with a descriptive and exploratory character and a qualitative approach, is an action research developed at the Sol Nascente State School, which is a school located in the rural area of ​​the municipality of Confresa/MT. Two educational projects were developed: "Reading is accurate, dreaming is inevitable" and "Reading is the way to learn". The study of pedagogical projects aimed at the rural education schools led us to realize the importance of inserting reading literary books as action within these projects. Based on the assumption that it is possible to collaborate with student learning, this study investigated the development of projects as well as teaching methods that meet the local specificity in this case a rural school. Therefore, the intention of this investigation was to analyze the development of educational projects as teaching methodology for such schools and teaching modalities.